The roominghouse madrigals early selected poems, 1946-1966 - Bukowski, Charles 1920-1994 (New York Ecco, 2002)
The Roominghouse Madrigals is a selection of poetry from Charles Bukowski's early work. It shows a slightly softer side to the beloved barfly.
Previously published by Black Sparrow Press.
Keywords: American poetry; Poetry